NMR imaging of materials - Blümich, Bernhard (Monographs on the physics and chemistry of materials, 2000)
Written for graduates, scientists and engineers, 'NMR Imaging of Materials' provides an introduction to a growing field. A large number of applications in basic research and quality control are now possible using NMR techniques.